Professional development program for physical education teachers in Indonesia - Mu'arifin Mu'arifin; Bagus Shandy Narmaditya (Jurnal Cakrawala Pendidikan, 2022)
Enhancing the quality of teachers has been a global challenge, and the government responded to this issue by providing various programs for teachers’ capacity upgrading This study aims at designing a professional development program for teachers of sports and health physical education in Indonesia. Using a research and development approach of Borg and Gall model, the study is to obtain comprehensive results and an understanding of the program. The preliminary findings indicate that the teachers face some obstacles in providing teaching and learning activities, although they have followed some coaching programs. The program development, therefore. proposed in this study consists of three primary documents: initiated program design, implementation guidelines, and evaluation prescription. Judgment by experts, principals, and teachers indicated that the program was proven valid, practical, and effective to be used as an assistance model for the professional development of sports and health physical education teachers in primary schools. The practical and managerial implications are also provided in this writing.